Distribuição espacial, amostragem sequencial e dinâmica populacional de Leptopharsa heveae (Hemiptera: Tingidae) na cultura da seringueira - Simonato, Adriano Luís [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the expansion of rubber trees in the northwestern region of São Paulo state, Brazil, the rubber-tree lacebug, Leptopharsa heveae, reached population levels that caused and continues to cause damages to heveiculture, reducing significantly the rubber production in these trees. To determine the spatial distribution of the lace bug and devise measures to control this pest, experiments were established in 3 areas where RRIM 600 rubber tree clones had been planted (ages 4, 8, and 12 years old), in a farm in the city of Guapiaçu, São Paulo. In each area, 100 parcels were considered, each one made by a line of 3 plants, being sampled 1 branch from the outer section of the lower-third of the canopy of the central plant in each parcel where the number of lacebug nymphs and adults was counted in 27 sampling dates. In each sample, the level of pest aggregation was studied by the dispersion indexes: variance/mean relationship, Morisita's index, Green's coefficient, Taylor's Power Law, and k exponent of the negative binomial; thus, it was verified that, in most samples, the L. heveae population presents aggregate distribution both for nymphs and adults, as well as the pest population as a whole (nymphs plus adults). The adjustment to the probability's distributions was studied through the chi-square test; the binomial negative distribution was the most appropriate model to represent the spatial distribution of the nymphs, adults, and the total population in the 3 areas. A sequential sampling plan was developed for the whole L. heveae population, with an expected maximum of 21 branches being sampled to determine whether preventive measures are necessary. The highest population averages of nymphs and adults of L. heveae occurred from July to October. It was found that the population of L. heveae was significantly influenced by rainfall, regardless of the age of the rubber trees

Com a expansão dos seringais na região Noroeste do Estado de São Paulo, o percevejo-de-renda da seringueira, Leptopharsa heveae, alcançou níveis populacionais que provocaram e têm provocado danos à heveicultura em geral, reduzindo de forma significativa a produção de látex nos seringais. Com o objetivo de conhecer a distribuição espacial para basear ações de controle desta praga, instalaram-se experimentos em 3 áreas de seringueira plantadas com o clone RRIM 600, com idades de 4, 8 e 12 anos, em uma fazenda localizada no município de Guapiaçu–SP. Em cada área foram consideradas 100 parcelas, cada uma composta por uma linha de 3 plantas sendo amostrado 1 ramo da parte externa do terço inferior da copa da planta central de cada parcela onde foram contadas ninfas e adultos, em 27 amostragens. O nível de agregação da praga foi estudado, para cada amostragem, segundo os índices de dispersão: razão variância/média, índice de Morisita, coeficiente de Green, lei de potência de Taylor e expoente k da binomial negativa e constatou-se que, na maioria das amostragens, a população de L. heveae apresentou distribuição agregada tanto para ninfas quanto para adultos e também para a população total (ninfas + adultos) da praga. Estudou-se o ajuste às distribuições de probabilidade através do teste qui-quadrado de aderência e o modelo mais adequado para representar a distribuição espacial foi a distribuição binomial negativa para ninfas, adultos e para o total da praga. Foi construído um plano de amostragem sequencial para a população total de L. heveae e o número máximo esperado é de 21 ramos para decidir se há a necessidade ou não do controle. As maiores médias populacionais de ninfas e adultos de L. heveae ocorreram no período de julho a outubro, e verificou-se que a população de L. heveae foi significativamente influenciada pelas chuvas, independente das idades ...
Keywords: Seringueira; Seringueira - Doenças e pragas; Pragas agricolas; Amostragem sequencial; Distribuição binomial; Percevejo (Inseto); Dispersão; Rubber plants